Under Stalin's shadow : a global history of Greek communism - Marantzidēs, Nikos A. (Northern Illinois University Press, an imprint of Cornell University Press, 2023)
"This book examines the history of the Communist party of Greece (KKE) between 1918 and 1956 from an international perspective. Because the frontiers between the national and the international in the Communist world were not so clearly separated, international Communist institutions, geopolitical soviet interests and sister parties' strategies shaped in fundamental ways the KKE's leadership, its character and decision-making mechanisms as a party, and the way of life of its followers"-- Provided by publisher.
Keywords: Kommounistiko Komma Helladas -- History -- 20th century.; Kommounistiko Komma Helladas; Communism -- Greece -- History -- 20th century.; HISTORY / Europe / Greece (see also Ancient / Greece).; Communism; Greece; Greece.; 20th century, c 1900 to c 1999.; European history.; Politics & government.; Marxism & Communism.; Politics and Government.; 1900-1999; Electronic books.; History